2019
DOI: 10.1007/s00334-019-00730-9
|View full text |Cite
|
Sign up to set email alerts
|

What was the ecological impact of a Trypillia megasite occupation? Multi-proxy palaeo-environmental investigations at Nebelivka, Ukraine

Abstract: Fine-resolution sampling of pollen, non-pollen palynomorphs and microcharcoal as well as sedimentological data in a 6-m sediment core were used to reconstruct both natural conditions and human impacts in the late fifth and early fourth millennia cal bc in the environs of the Nebelivka megasite in Kirovograd Oblast, Central Ukraine. This 238-ha site, dating to the Middle (or BII) Phase of the Trypillia culture, represents one of the first low-density urban establishments in Europe. Despite what was believed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…Tilia, and more particularly Corylus, are important taxa in palynological records (Albert et al 2019), but they were not identified among the charcoal fragments in our study. Regarding Tilia, its rarity in charcoal records compared to its representation in palynological diagrams is common at Neolithic sites, particularly in temperate Europe (Bakels 1992;Van der Sloot et al 2003;Salavert et al 2018).…”
Section: -5000 Cal Bc) In Southern Bugcontrasting
confidence: 56%
See 1 more Smart Citation
“…Tilia, and more particularly Corylus, are important taxa in palynological records (Albert et al 2019), but they were not identified among the charcoal fragments in our study. Regarding Tilia, its rarity in charcoal records compared to its representation in palynological diagrams is common at Neolithic sites, particularly in temperate Europe (Bakels 1992;Van der Sloot et al 2003;Salavert et al 2018).…”
Section: -5000 Cal Bc) In Southern Bugcontrasting
confidence: 56%
“…In the western Ukraine area, the few existing pollen sequences that covers the Early Atlantic period (6900-4700 cal BC) are not well dated (Pashkevich 1982, Kremenetski 1995, Vinogradova and Kiosak 2007. These limited pollen studies indicate that around 5000 cal BC, the forest-steppe vegetation was characterized by thermophilous mixed-oak woodlands, mainly composed of Corylus (hazelnut), Ulmus (elm), Tilia (lime tree), Quercus and some Carpinus (Albert et al 2019). Bohn et al 2000).…”
Section: -Environmental Settingmentioning
confidence: 99%
“…Wengrow & Graeber 2015), while the third relies on smaller-scale permanent settlement. Each model presents a variant on the Nebelivka site biography, which began with a well-established settlement network in the Southern Bug catchment, some of whose site clusters included megasites of up to 150 ha (for origins, see Chapman et al 2019), and a local settlement near the Nebelivka promontory, as attested in the Nebelivka 1B pollen core (Albert et al 2019).…”
Section: Alternative Models For Nebelivkamentioning
confidence: 99%
“…A 6 m sediment core from a valley 250 m from the edge of the megasite has provided a dated sequence of local vegetation and megasite human impacts (Albert et al 2019) (Fig. 10).…”
Section: Households Neighbourhoods and Quartersmentioning
confidence: 99%
“…Alternatively, they may have provided permanent habitation in smaller numbers of contemporaneously occupied houses (Albert et al . 2020). Houses were organised into neighbourhoods (Rassmann et al .…”
Section: Introductionmentioning
confidence: 99%